THE IMPACT OF CLAIM EXPENSES, UNDERWRITING RISK, PROFITABILITY, COMPANY SIZE AND RETENTION RATIO ON SOLVENCY OF INSURANCE INDUSTRY - Sutanto, Shelby; Lesmana, Iwan; Sitardja, Meco; Bintara, dheny (Indonesian Journal of Accounting and Governance, 2023)
The main purpose of this research is to analyze Claim Expenses, Underwriting Risk, Profitability, Company Size, and Retention Ratio on Solvency of Insurance Industry. The purpose of this research is to help future investors in choosing the right insurance company. This research was a quantitative descriptive research method. The sample used in this research is secondary data of Insurance Industry on the period from 2015 to 2020. Using SPSS (statistical package for the social sciences), methods of analysis used in this study include tolerance and VIF test, Kolmogorov-Smirnov test, multivariate cointegration tests: Test, SRESID and ZPRED estimation, t-statistical tests, F-statistical test, coefficient of determination (R²), and Pearson Correlation Product Moment.The result of this research shows claim expense, underwriting risk, ROA, and company size have significant influence on insurance industry’s solvency, but retention ratio has no significant influence on insurance industry’s solvency. All the independent variables simultaneously from a good model to explain the solvency since the magnitude of the effect value is 83,4%, while remaining 16,6% is explained by other variables besides claim expense, underwriting risk, ROA, company size, and retention ratio. The linear regression produced a formula to calculate the solvency, so this formula could be used in monitoring the financial health of an insurance company.